Transcriptomic Analysis Reveals the Metabolic Mechanism of L-Ascorbic Acid in Ziziphus jujuba Mill. - Zhang, Chunmei; Huang, Jian; Li, Xingang (Frontiers in Plant Science, 2016)
Chinese jujube (Ziziphus jujuba Mill.) is the most economically important member of the Rhamnaceae family and contains a high concentration of ascorbic acid (AsA). To explore the metabolic mechanism of AsA accumulation, we investigated the abundance of AsA in the fruit development stages, the leaf and flower of Z. jujuba cv Junzao, and the mature fruit of one type of wild jujube (Z. jujuba var. spinosa Hu, Yanchuan sour jujube). And the expression patterns of genes involved in AsA biosynthesis, degradation and recycling were analyzed. The result showed that AsA biosynthesis during early fruit development (the enlargement stage) is the main reason for jujube high accumulation. The L-galactose pathway plays a predominant role in the biosynthesis of AsA during jujube fruit development, and the genes GMP1, GME1, GGP, and GaLDH involved in the determination of AsA concentration during fruit development and in different genotypes; the myo-inositol pathway along with the genes GME2 and GMP2 in the L-galactose pathway play a compensatory role in maintaining AsA accumulation during the ripening stage. These findings enhance our understanding of the molecular mechanism in regulating AsA accumulation for jujube.